Experimental investigation on influences of methanol reformate impurities in performances of high temperature proton exchange membrane fuel cells. (26th May 2023) - Xu, Jiawei; Zhao, Yawen; Wu, Yuhua; Wang, Yifei; Xiao, Shengying; Xu, Xinhai
Abstract: Even though the methanol reformate can be fed into the high temperature proton exchange membrane fuel cell, the influences of different reformate components on the fuel cell are still unclear. This work investigates the effects of CO, CO2, H2 O, and CH3 OH in the fuel gas on the fuel cell performances. The distribution of relaxation times and equivalent circuit model are employed for analysis. The results show the increase of anodic charge and mass transfer resistances are main factors of CO poisoning which results in 77 mV overpotential. The maximum overpotential difference between CO2 and Ar is only 4 mV, which means the dilution effect of CO2 is similar to Ar. H2 O decreases the Ohmic and anodic charge transfer resistances and reducing the overpotential by 10 mV. CH3 OH below 3% has slight positive effect on the fuel cell performance. However, 5% CH3 OH results in high overpotential of 36 mV. Graphical abstract: Image 1 Highlights: A HT-PEMFC was experimentally tested with various fuel impurities. Effects of 1–2% CO, 10–30% CO2, 5–20% H2 O and 1–5% CH3 OH were examined. 2% CO concentration causes 77 mV overpotential. 20% H2 O concentration reduces 10 mV overpotential. Resistances related to Ohmic, mass transfer and charge transfer were identified.